A quase-experimentação no estudo da cultura: análise da obra Colapso de Jared Diamond - Sampaio, Angelo Augusto Silva (2008)
Behavior Analysis has yet to establish a productive research program about culture, cultural practices and their evolution. Although conceptual problems (about the appropriate units of analysis and the complexity of cultures) and methodological issues (there aren t well tested procedures to explore cultural phenomena within a behavior analytic perspective) are at the root of this absence, the conceptual issues have been tackled by some (S. Glenn and M. Harris, for instance). These efforts have not been followed, until now, by validating empirically based studies. We suggest that quasiexperimental studies may be a productive alternative to this problem. Quasiexperimental studies should allow the description of functional relations among events: The experimental manipulation, and therefore, control, is limited in such cases, but there are empirically based measurements of dependent variables when independent variables are present and absent. J. Diamond s scientific position seems to be compatible with philosophical and methodological tenets of Behavior Analysis and Diamond has repeatedly argued for quasi-experimentation as a method to study culture and cultural evolution. The present work focuses were: to explore the possibilities opened by quasi experimental procedures on the study of culture and to further explore Glenn s and Harris interpretations of culture. In order to do it Diamond s book Colapse was analyzed. Diamond s interpretation of the Viking colonies fate was taken as the exemplar. Exerts interpreted as elements of Diamond s construction of quasiexperiments about the Viking colonies were selected and their procedural elements and main results were evaluated. The present results suggest that quasi-experimentation may be a valuable methodological alternative to the empirically based study of culture. Possible relationships between Diamond s results and Glenn s proposition of metacontingencies and macrocontingencies as units of analysis at the cultural level of selection and Harris principle of infra-structural determinism of cultures are discussed. Diamond s distinction between proximate and ultimate causes indicates a relevant separation between variables for the analysis of present and past cultures. The present work also points out methodological aspects pertinent to the implementation of quasiexperimental studies on culture